2000
DOI: 10.1007/s002280050708
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation of the urinary 6β-hydroxycortisol to cortisol ratio that would reflect hepatic CYP3A activity

Abstract: The result indicates that imprudent use of random urine has a great risk of false evaluation in assessment of the 6beta-hydroxycortisol to cortisol ratio and that the ratio in 24-h urine samples provides a more robust measure of the inter-individual difference of this metabolic ratio, which to a certain but not complete extent represents the CYP3A activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 19 publications
4
45
1
Order By: Relevance
“…The urine F concentration decreased during the afternoon and the urinary 6b-OHF/F ratio exhibited significant diurnal variation with a peak between 1,300 and 2,100 (Table 3). These results are in good agreement with previous reports [12,13]. It was suggested that the diurnal variation of the urinary 6b-OHF/F ratio may infer the circadian rhythm of hepatic CYP3A activity [12] although it may just reflect the variation in the availability of the substrate F.…”
Section: Clinical Applicationsupporting
confidence: 91%
“…The urine F concentration decreased during the afternoon and the urinary 6b-OHF/F ratio exhibited significant diurnal variation with a peak between 1,300 and 2,100 (Table 3). These results are in good agreement with previous reports [12,13]. It was suggested that the diurnal variation of the urinary 6b-OHF/F ratio may infer the circadian rhythm of hepatic CYP3A activity [12] although it may just reflect the variation in the availability of the substrate F.…”
Section: Clinical Applicationsupporting
confidence: 91%
“…Some results have shown the absence of any changes in the ratio of 6b-OHF/F in spot urine throughout the day (Galteau and Shamsa, 2003;Micuda et al, 2007). Conversely one report indicated a diurnal rhythm, with increased levels in the evening (Ohno et al, 2000). It should be noted that the urinary ratio 6b-OHF/F is valid as the index for in vivo CYP3A activity only when the renal clearance of cortisol is consistent (Furuta et al, 2001(Furuta et al, , 2003Peng et al, 2011), because the urinary ratio 6b-OHF/F is a function of two independent parameters: metabolic clearance specific for 6b-hydroxylation and renal clearance of cortisol.…”
Section: Discussionmentioning
confidence: 99%
“…Some endogenous markers have been in use for decades, such as the urinary 6b-hydroxycortisol/cortisol metabolic ratio (reviewed in Galteau and Shamsa, 2003), whereas others such as 4b-hydroxycholesterol or 4b,25-dihydroxyvitamin D 3 were identified more recently (Bodin et al, 2001;Wang et al, 2012). Because the formation and subsequent excretion of cortisol follows a diurnal pattern, the 6b-hydroxycortisol/ cortisol ratio determined over a long urine collection interval (e.g., 24 hours) is typically reported, rather than the concentration of metabolite alone (Ohno et al, 2000;Hu et al, 2009;Luo et al, 2009). Despite numerous studies with urinary 6b-hydroxycortisol, several reports demonstrate a lack of correlation with CYP3A substrates, especially under basal conditions (Chen et al, 2006;Luo et al, 2009;Dutreix et al, 2014).…”
Section: Interindividual Variability In Cyp2d6-mediated Drugmentioning
confidence: 99%